Student’s Sense of School Belonging: Home Influence - Dukynaitė, Rita; Dudaitė, Jolita (Pedagogika, 2017)
Family and school play the leading role in personality formation and its further development. Family is the centre of social and emotional world for small children. However, in the adolescence period, students start seeking recognition at school and among friends; the need for involvement, achievement and leadership shows up. Although, at first sight, family remains in the background, yet its role at the fundamental moments of student’s life remains significant. Sense of school belonging is a concept which defines the extent to which students feel personally accepted, respected, involved and supported by parents, teachers, other community members in school environment. Student’s sense of school belonging primarily depends on teachers; however, acceptance and appraisal of a child by classmates and parents is also important to the sense of belonging. The sense of school belonging shows the extent to which students are involved in and connected with school community (both teachers and students) and feel support and assistance. It is a subjective assessment of a student which is related to the feeling of respect and acceptance at school, i.e. psychological membership in school and classroom. Although a teacher and school still play one of the key roles in fostering the sense of acceptance and school belonging, yet attitude of family members towards school, as well as certain factors of home educational environment strengthen or weaken the sense of belonging. Good relationship of teacher and student with school, teachers and peers influences students’ inclination for further development and fully fledged membership in social group. Lack of interrelationship may have a negative impact on student’s self-awareness, life satisfaction and interest in learning activity. This article analyses which factors of home educational environment have influence on the formation of student’s sense of school belonging. 4 618 students aged 15 from 216 general and vocational schools participated in the survey.